BDNF gene delivery mediated by neuron-targeted nanoparticles is neuroprotective in peripheral nerve injury - Lopes, CDF (2017)
Neuron-targeted gene delivery is a promising strategy to treat peripheral neuropathies. Here we propose the use of polymeric nanoparticles based on thiolated trimethyl chitosan (TMCSH) to mediate targeted gene delivery to peripheral neurons upon a peripheral and minimally invasive intramuscular administration. Nanoparticles were grafted with the non-toxic carboxylic fragment of the tetanus neurotoxin (HC) to allow neuron targeting and were explored to deliver a plasmid DNA encoding for the brain-derived neurotrophic factor (BDNF) in a peripheral nerve injury model. The TMCSH-HC/BDNF nanoparticle treatment promoted the release and significant expression of BDNF in neural tissues, which resulted in an enhanced functional recovery after injury as compared to control treatments (vehicle and non-targeted nanoparticles), associated with an improvement in key pro-regenerative events, namely, the increased expression of neurofilament and growth-associated protein GAP-43 in the injured nerves. Moreover, the targeted nanoparticle treatment was correlated with a significantly higher density of myelinated axons in the distal stump of injured nerves, as well as with preservation of unmyelinated axon density as compared with controls and a protective role in injury-denervated muscles, preventing them from denervation. These results highlight the potential of TMCSH-HC nanoparticles as non-viral gene carriers to deliver therapeutic genes into the peripheral neurons and thus, pave the way for their use as an effective therapeutic intervention for peripheral neuropathies.